1982
DOI: 10.1098/rstb.1982.0107
|View full text |Cite
|
Sign up to set email alerts
|

How does interferon inhibit tumour growth?

Abstract: Interferon can inhibit tumour growth in experimental animals and in some patients with benign and malignant tumours. There is experimental evidence to suggest that several mechanisms may be involved: a direct effect on the tumor or an indirect effect via the host, or both. Thus, interferon may slow the rate of tumour cell multiplication and this may lead to cell death. Interferon may induce changes in the cell surface rendering tumour cells more sensitive to host defence mechanisms. Interferon may induce rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
1

Year Published

1984
1984
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 36 publications
2
27
1
Order By: Relevance
“…(1986), the mouse L1210 and Colo 26 cells used were resistant to NK cell lysis and both groups concluded that NK cells were unlikely to be responsible for the anti-tumor effects observed. In fact, neither our previous work (Belardelli et al, 1983;Gresser, 1985) nor histologic examination of the livers of interferon-treated tumor inoculated mice (Fig. 6) suggest that host immune cells are an important component of the anti-tumor action of interferon; nor have we previously found any evidence for a soluble cytotoxic factor (Belardelli et al, 1982b;Gresser, 1985).…”
Section: Days After Tumor Inoculationmentioning
confidence: 76%
“…(1986), the mouse L1210 and Colo 26 cells used were resistant to NK cell lysis and both groups concluded that NK cells were unlikely to be responsible for the anti-tumor effects observed. In fact, neither our previous work (Belardelli et al, 1983;Gresser, 1985) nor histologic examination of the livers of interferon-treated tumor inoculated mice (Fig. 6) suggest that host immune cells are an important component of the anti-tumor action of interferon; nor have we previously found any evidence for a soluble cytotoxic factor (Belardelli et al, 1982b;Gresser, 1985).…”
Section: Days After Tumor Inoculationmentioning
confidence: 76%
“…It is now firmly established that in addition to inhibiting virus replication interferons can also inhibit cell multiplica- (24), cause reversion of the transformed phenotype (2), and exert antitumor activity in both experimental animals and humans (11,18). The molecular mechanism(s) underlying many of these effects, however, remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clearance of radiolabelled Taylor-Papadimitriou, 1980), they can alter the state of tumour cell differentiation (Rossi, 1985), modulate surface antigen expression (Rosa et al, 1986), inhibit oncogene/expression and levels of oncogene product (Jonak & Knight, 1986), and induce reversion of the transformed phenotype to a normal phenotype (Brouty-Boye & Gresser, 1981). All these direct actions may play a role in limiting tumour spread.Interferons can also act on the tumour via their action on host defence cells (Gresser & Bourali-Maury, 1972;Gresser & Tovey, 1978;Gresser, 1985 Human tumour xenografts growing in nude mice serve as good models to dissociate the direct effects on human tumour from indirect effects on the murine host because of species specificity of the IFNs. Balkwill et al (1982, 1985) have shown that HuIFNs directly inhibit the growth of subcutaneous human bowel, breast, lung and ovarian cancers in nude mice.…”
mentioning
confidence: 99%
“…Interferons can also act on the tumour via their action on host defence cells (Gresser & Bourali-Maury, 1972;Gresser & Tovey, 1978;Gresser, 1985 Human tumour xenografts growing in nude mice serve as good models to dissociate the direct effects on human tumour from indirect effects on the murine host because of species specificity of the IFNs. Balkwill et al (1982, 1985) have shown that HuIFNs directly inhibit the growth of subcutaneous human bowel, breast, lung and ovarian cancers in nude mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation